2005
DOI: 10.1007/s00701-005-0682-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of aneurysms of the internal carotid artery bifurcation

Abstract: ICBi aneurysms were deviated to the side of the A1 segment of the ACA, where the artery might suffer higher hemodynamic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…27,29,30 The bifurcation angle may affect disease formation at the apex by influencing the tensile or stretching forces at the arterial bifurcation. 31 The bifurcation angle may affect the formation of flow turbulence near the bifurcation apex. 32 After studying the characteristics of aneurysms on the ICA bifurcation, Sakamoto et al 31 reported that all the ICA bifurcation aneurysms deviated to the side of the A1 segment of the anterior cerebral artery, which formed a smaller angle with the ICA than that formed between the MCA and the ICA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,29,30 The bifurcation angle may affect disease formation at the apex by influencing the tensile or stretching forces at the arterial bifurcation. 31 The bifurcation angle may affect the formation of flow turbulence near the bifurcation apex. 32 After studying the characteristics of aneurysms on the ICA bifurcation, Sakamoto et al 31 reported that all the ICA bifurcation aneurysms deviated to the side of the A1 segment of the anterior cerebral artery, which formed a smaller angle with the ICA than that formed between the MCA and the ICA.…”
Section: Discussionmentioning
confidence: 99%
“…31 The bifurcation angle may affect the formation of flow turbulence near the bifurcation apex. 32 After studying the characteristics of aneurysms on the ICA bifurcation, Sakamoto et al 31 reported that all the ICA bifurcation aneurysms deviated to the side of the A1 segment of the anterior cerebral artery, which formed a smaller angle with the ICA than that formed between the MCA and the ICA. Their result suggested higher hemodynamic stress experienced on the side of the A1 segment.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The presence of multiple perforators in this area along with the angle of origin (often skewed toward the MCA or the anterior cerebral artery primarily) can make treatment challenging. 3 Additionally, the increased hemodynamic stress at this level translates into a higher rate of recurrence compared with aneurysms in other locations.…”
mentioning
confidence: 99%
“…Internal carotid artery (ICA) bifurcation aneurysms are uncommon, only accounting for about 2%-9% of intracranial aneurysms (11,16,19,22). Clipping is challenging for neurosurgeons due to their deep location, and vital perforators surrounding or adherent to the aneurysms (8,11,16).…”
Section: Discussionmentioning
confidence: 99%
“…Van Rooij et al ever reported the endovascular treatment for ICA bifurcation aneurysm, and the result was thought to be comparable with surgical results (7,22). However, the aneurysms located at ICA bifurcation often harbor wide necks, which may limit the usage of coiling of the aneurysms (7,19,22). Besides, the fusiform aneurysms are also difficult to be embolized by coils alone.…”
Section: Clinical and Angiographic Follow-upmentioning
confidence: 99%